Disparities in prevalence of heart failure between the genders in relation to age, multimorbidity and socioeconomic status in southern Sweden: a cross-sectional study - Mia Scholten; Patrik Midlöv; Anders Halling (Taylor & Francis Group, 2023)
AbstractObjective Prior studies have reported that heart failure typically affects elderly, multimorbid and socioeconomically deprived men. Women with heart failure are generally older, have a higher EF (ejection fraction) and have more heart failure-related symptoms than men. This study explored the disparities in the prevalence of heart failure between men and women in relation to age, multimorbidity level and socioeconomic status of the population in southern Sweden.Design A register-based, cross-sectional cohort study.Setting and subjects: The inhabitants from 20 years of age onwards (N = 981,383) living in southern Sweden in 2015.Main outcome measure: Prevalence and mean probability of having heart failure in both genders. CNI (Care Need Index) percentiles depend on the socioeconomic status of their listed primary healthcare centres.Results Men had a higher OR for HF − 1.70 (95% CI 1.65-1.75) - than women. The probability of men having heart failure increased significantly compared to women with advancing age and multimorbidity levels. At all CNI levels, the multimorbid patients had a higher prevalence of heart failure in men than in women. The disparity in the mean probability of heart failure between the most affluent and deprived CNI percentile was more apparent in women compared to men, especially from 80 years.Conclusions The prevalence of heart failure differs significantly between the genders. Men had an increasing mean probability of heart failure with advancing age and multimorbidity level compared to women. Socioeconomic deprivation was more strongly associated with heart failure in women than in men. The probability of having heart failure differs between the genders in several aspects.Key PointsIndependently of socioeconomic status, men had a higher prevalence of heart failure than women among the multimorbid patients.The mean probability of men having heart failure increased significantly compared to women with advancing age and multimorbidity level.Socioeconomic status was more strongly associated with heart failure in women than in men.